Respostas

2014-05-21T15:30:35-03:00
A)x²-9x=0  onde a=1  b=-9   c=0


Δ=b²-4.a.c
Δ=(-9)²-4.1.0
Δ=81-0
Δ=81   ⇒raiz de 81 é 9



x'=-(-9)+9   +9+9      18
   ¨¨¨¨¨¨¨¨¨¨ = ¨¨¨¨¨¨¨¨ =  ¨¨¨¨¨¨=   9
       2.1         2          2


x"=-(-9)-9    +9-9       0        
    ¨¨¨¨¨¨¨¨¨¨=  ¨¨¨¨¨¨¨¨= ¨¨¨¨¨¨ = 0                S:(9, 0)
        2.1        2        2 



B)x²+6x+8=0   onde a=1    b=6     c=8
 
 Δ=b²-4.a.c
 Δ=(6)²-4.1.8
Δ=36-32
Δ=4  ⇒raiz de 4 é 2


x'=-6+2     -4      
   ¨¨¨¨¨¨¨¨ = ¨¨¨¨¨¨ = -2
       2.1      2


x"=-6-2      -8
   ¨¨¨¨¨¨¨¨ =  ¨¨¨¨¨¨ = -4
      2.1        2                              S:(-2, -4)





C)x²-14-49=0  onde a=1  b=-14   c=49 


Δ=b²-4.a.c
Δ=(-14)²-4.1.49
Δ=196-196
Δ=0  ⇒raiz de 0 é 0



x'=-(-14)+0      +14
   ¨¨¨¨¨¨¨¨¨¨¨¨ =   ¨¨¨¨¨¨  =  7
        2.1           2 


x"=-(-14)-0       +14
    ¨¨¨¨¨¨¨¨¨¨¨¨  = ¨¨¨¨¨¨¨¨ = 7                    S:(7, 7)
        2.1            2

1 5 1